2009
DOI: 10.1007/s00381-009-0934-3
|View full text |Cite
|
Sign up to set email alerts
|

Cervical osteochondroma with postoperative recurrence: case report and review of the literature

Abstract: The child was reoperated and the lesion removed along with the entire remaining lamina of C3. At 6-year follow-up, there has been no recurrence of the child's cervical lesion. We believe this to be the third reported case of recurrence of a cervical osteochondroma. Surgeons dealing with such lesions should be mindful of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Most osteochondromas arise in the appendicular skeleton and occur as solitary or multiple exostosis. 35,38,65 The latter is part of an inherited, autosomal dominant condition called hereditary multiple exostosis. 65 These lesions arise from epiphyseal herniation with a displaced portion of cartilage and hence the cartilaginous cap.…”
Section: Primary Bone Tumors Affecting the Atlantoaxial Skeleton Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Most osteochondromas arise in the appendicular skeleton and occur as solitary or multiple exostosis. 35,38,65 The latter is part of an inherited, autosomal dominant condition called hereditary multiple exostosis. 65 These lesions arise from epiphyseal herniation with a displaced portion of cartilage and hence the cartilaginous cap.…”
Section: Primary Bone Tumors Affecting the Atlantoaxial Skeleton Of Cmentioning
confidence: 99%
“…13,39,51,59,60,64 Tubbs et al reported on a rare case of recurrent osteochondroma after incomplete resection. 65 Our literature review indicated that all patients with multiple hereditary exostosis should undergo MRI of the spine because 27% will have spinal lesions.…”
Section: Primary Bone Tumors Affecting the Atlantoaxial Skeleton Of Cmentioning
confidence: 99%
“…16 Some argue that osteochondromas are not true neoplasms but rather hamartomas herniating from the epiphyseal growth cartilage before children reach skeletal maturity. 2,13,23,29 These lesions are not usually identified until adulthood, with a mean age of 39 years at diagnosis. 26 Given that these exophytic growths arise from the posterior elements of the spine, osteochondromas are commonly managed with posterior resection.…”
mentioning
confidence: 99%
“…2 Only 1% to 4% of cases involve the spine, of which half involve the cervical spine, making cervical spine osteochondroma a rare entity. [3][4][5] Two cases of solitary osteochondroma arising from the anterior aspect of the vertebral bodies of C2 and C7 have been reported 4,6 ; however, none have been reported for C4. We report the first case of solitary osteochondroma arising from the anterior body of C4.…”
mentioning
confidence: 99%